Tentang Harmoni antara Tuhan, Manusia dan Alam dalam Tradisi Beduruk di Dusun Medang - Fransiskus Gregorius Nyaming (Litbang STFT Widya Sasana Malang, 2019)
In this paper the author focuses on the theme of harmony by using the Beduruktradition in Medang hamlet as a starting point for reflection. The harmony in question is harmony between man and God, between man and fellowman and between man and nature. The author believes that so far the beduruk tradition has contributed to the values and wisdoms that are needed to build that harmonies. The emphasis on the theme of harmony actually departs from the author’s own concern about the destruction of nature and the environment, especially in Indonesia. Therefore, through this discussion, the authors hope that whatever forms of human work in cultivating nature, always respect the Creator, respect for human dignity, and respect for nature.